Analysis Of Maternal Knowledge Levels Regarding Immunization And Its Impact On Children's Immunity At The Ponre Bulukumba Community Health Center - Khaylah Rayyani; Nur Ismih Amaliah; A.Nidha Eka Restuti Munawir; Putri Indrayani Larashati; Mutmainna Mutmainna (CV. AFDIFAL MAJU BERKAH, 2026)
Immunization is one of the most effective health interventions for preventing infectious diseases in children. Mothers’ knowledge about immunization plays a crucial role in vaccination decisions, which in turn influences the child’s immune status. This study aims to analyze the level of maternal knowledge regarding immunization and its effect on children’s immunity at the Ponre Health Center, Bulukumba. The research employed a quantitative approach with a cross-sectional design. A sample of 100 mothers with children under five was selected using purposive sampling. Data were collected through questionnaires and observations of the children’s immune status based on health records. Data analysis was conducted using the chi-square test. The results showed that 60% of the mothers had good knowledge about immunization, and there was a significant relationship between maternal knowledge and children’s immune status (p < 0.05). The study concludes that good maternal knowledge contributes positively to children’s immunity; therefore, continuous education is necessary.